Disseminated lomentosporiosis in a heart transplant recipient: Case report and review of the literature. Issue 4 (18th February 2021) - Valerio, Maricela; Vásquez, Víctor; Álvarez‐Uria, Ana; Zatarain‐Nicolás, Eduardo; Pavone, Paolo; Martínez‐Jiménez, María del Carmen; Barrio‐Gutiérrez, José María; Cuerpo, Gregorio; Guinea‐Ortega, Jesús; Vena, Antonio; Peligros‐Gómez, María Isabel; Bouza, Emilio; et al.
Abstract: Background: Lomentospora prolificans (formerly S prolificans ) is a saprophyte fungi that causes opportunistic infections in solid organ transplant (SOT) recipients. Resulting disseminated infections are difficult to treat and have a high mortality. Indications for antifungal prophylaxis after heart transplantation (HT) include CMV disease, reoperation, renal replacement therapy, extracorporeal membrane oxygenation (ECMO), and high environmental exposure to Aspergillus spores. However, the risk of breakthrough infections, such as Lomentosporiosis, remains a cause of concern. Methods: We report the clinical findings, microbiology, treatment and outcome of a disseminated Lomentosporiosis in a heart transplant recipient with ECMO and antifungal prophylaxis. Results: A 25‐year‐old male with complex grown‐up congenital heart disease (GUCHD) was admitted for HT. He presented severe post‐surgical complications including acute kidney injury and right heart and respiratory failure requiring venoarterial‐ECMO, continuous renal replacement therapy (CCRT) and later on (+14) a ventricular assist device (VAD). Ganciclovir, cotrimoxazole, and antifungal prophylaxis with anidulafungin at standard doses had been started on day + 3 post HT. The patient presented seizures (+4), pancytopenia with mild neutropenia (days + 6 to + 11), influenza B (+7), and bacteremic Pseudomonas aeruginosa ventilator associated pneumonia (VAP) (+10). On days + 14 to + 16 Lomentospora prolificans was recovered from blood cultures, broncho aspirate, catheter tip, and skin biopsy. Despite treatment with L‐AMB, voriconazole and terbinafine the patients died on day 17 after HT. Necropsy revealed disseminated infection with fungal invasion in central nervous system, heart, lung, cutaneous, and subcutaneous tissue. Broth microdilution tests demonstrated resistance to all antifungals. Conclusions: Lomentosporiosis is a rare complication that may emerge as a breakthrough invasive fungal infection in heart transplant recipients on ECMO despite antifungal prophylaxis.